2017
DOI: 10.1111/ldrp.12125
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐service Teachers’ Interpretation of CBM Progress Monitoring Data

Abstract: Teachers must be proficient at using data to evaluate the effects of instructional strategies and interventions, and must be able to make, describe, justify, and validate their data-based instructional decisions to parents, students, and educational colleagues. An important related skill is the ability to accurately read and interpret progress-monitoring graphs. This study examined preservice special education teachers' graph reading and interpretation skills at two points in time. Participants used a think-al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 19 publications
4
50
1
Order By: Relevance
“…Completeness scores in the current study were higher than those found in previous research. Wagner et al (2017) reported that preservice teachers mentioned only three of nine possible graph elements, and van den Bosch et al (2017) reported that inservice teachers mentioned six of nine graph elements. The higher completeness scores in the present study (seven of eight graph elements) may be due to the fact that teachers were asked to describe the graphs as if they were describing them to a parent rather than to tell all they were seeing and thinking about a graph, as was done in the previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Completeness scores in the current study were higher than those found in previous research. Wagner et al (2017) reported that preservice teachers mentioned only three of nine possible graph elements, and van den Bosch et al (2017) reported that inservice teachers mentioned six of nine graph elements. The higher completeness scores in the present study (seven of eight graph elements) may be due to the fact that teachers were asked to describe the graphs as if they were describing them to a parent rather than to tell all they were seeing and thinking about a graph, as was done in the previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…At both pre- and posttest, graph comprehension was assessed via a CBM Graph-Description Task. In previous research, the CBM Graph-Description Task has been shown to differentiate graph comprehension of (a) preservice teachers from that of CBM experts ( Wagner et al, 2017 ), (b) inservice teachers from CBM experts ( van den Bosch et al, 2017 ), and (c) teachers with higher ratings versus lower ratings on understanding and interpreting CBM graphed data ( Espin et al, 2017 ). As an example, in the study by van den Bosch et al (2017) , scores on the CBM Graph-Description Task for inservice teachers versus CBM experts were, respectively, 97.5% versus 100% for accuracy, 5.7 versus 8.3 for completeness, 51.7% versus 85% for sequential coherence, 1.7 versus 4.8 for data-to-data comparisons, 1.7 versus 4.1 for data-to-goal comparisons, and 1 versus 5 for data-to-instructional links (see following section for a detailed description of these variables).…”
Section: Methodsmentioning
confidence: 99%
“…Another suggestion is that teachers in Germany should be made aware about the idea of data-based decision-making. This topic should already be given a stronger focus in university education (Wagner et al, 2017), but also to teachers already working in school practice (Espin et al, 2017). In the literature there is a lack of evaluated concepts for further training and coaching of teachers for a safe handling of data in the sense of a data-based decision-making approach.…”
Section: Suggestionsmentioning
confidence: 99%
“…Assessment can allow teachers to determine where errors are occurring and implement effective practices to meet the learner’s needs. However, though teachers frequently assess their students’ learning, they often struggle to make data-based decisions that positively affect student achievement (Mandinach & Jimerson, 2016; Riccomini, 2005; Stecker & Fuchs, 2000; Wagner et al, 2017).…”
Section: Special Education Teachers As Mathematics Teachersmentioning
confidence: 99%